Cox’s Bazar Panel Survey, Rapid Follow-up Round 2 : Status of Education Among School-Aged Children in Cox’s Bazar - World Bank (World Bank, Washington, DC, 2021)
This brief summarizes findings from rapid welfare tracking surveys in Cox’s Bazar. Two rounds of tracking surveys were implemented via phone interviews in 2020 to monitor the impacts of the Coronavirus (COVID-19) crisis on labor markets, wages, and household coping strategies. The first round was conducted during the COVID-related lockdowns in April-May 2020. A second round was conducted from October-December 2020, roughly six months after the government-imposed lockdowns, and also included a short module on education. Within the host community, the survey was further stratified into high exposure (HE, within three hours walking distance of a Rohingya camp) and low exposure (LE, more than three hours walking distance from a Rohingya camp) areas within the district.